Embedded systems hardware for software engineers - Lipiansky, Ed (McGraw-Hill, 2012)
"'Embedded Systems Hardware for Software Engineers' describes the electrical and electronic circuits that are used in embedded systems, their function, and how they can be interfaced to other devices." -- P.4 of cover.